Kebijakan Pendidikan dalam Meningkatkan Profesionalitas Guru - Muhammad Iqbal; Audy Andini Lubis; Muhammad Sibral Malasi; Nur Afni; Wanda Zuhro Syam Pratami (Departement of Mathematics Education, 2023)
Professionalism of teachers and lecturers is the ability of teachers and lecturers to apply and be consistent with their competencies when carrying out tasks, such as the teacher's ability to be able to develop potential and arouse students' interest, have self-confidence, be able to provide motivation and inspiration to students, visionary, innovative towards learning, able to control yourself, commitment, and responsibility. The education policy made by the government to continue to develop the teaching profession as a profession that is strong and respected along with other professions can be seen from the enactment of Law No. 14 of 2005 concerning Teachers and Lecturers which seeks to develop the teaching profession through legal protection. This journal discusses the urgency of the teaching profession in which the teacher has a strategic role and position in the implementation of the teacher as the front guard and a pioneer of educational success. In addition, this journal will also describe issues and phenomena from public policy by including the process of analyzing and implementing public policy. The conclusion of this journal is leaning towards the existence of teachers in education, the authors view that teachers are not only a profession but rather as companions, educators, teachers, directors and determinants of educational outcomes. Therefore the government must be able to accommodate efforts to improve and develop teachers as well as in the process of monitoring teachers after training or various other improvement efforts.